2022
DOI: 10.1177/16094069221080301
|View full text |Cite|
|
Sign up to set email alerts
|

Bridging Indigenous and Western Methods in Social Science Research

Abstract: This paper presents a method for how grounded theory can be used to bridge Western and Indigenous approaches to research, and how these epistemologies may complement each other. The objective in presenting this method is to contribute to the ongoing conversation on how best to integrate these two frameworks. As historically in social science research western methodologies have been preferred over Indigenous methodologies, this integration serves both to further reconciliation and to enhance methodological rigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Whilst the researchers maintain influence over the research design and interpretation, interviews were sought as a method to best coconstruct the findings and the theory posited with participants to explain the central research question (Charmaz, 2006;Metelski et al, 2021). This approach, in tandem with a constructionist grounded theory (CGT) method, was used to maintain a strength-based approach to the research (Coghlan & Brydon-Miller, 2014), where Indigenous participants' direct expertise, experiences and perspectives concerning successful Indigenous employment outcomes are central to the research findings (Charmaz, 2000;Quinn, 2022). CGT is an adaptation of the original concept of grounded theory posited by Glaser and Strauss (1967), coined by Charmaz (2000Charmaz ( , 2006.…”
Section: Et Hodmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst the researchers maintain influence over the research design and interpretation, interviews were sought as a method to best coconstruct the findings and the theory posited with participants to explain the central research question (Charmaz, 2006;Metelski et al, 2021). This approach, in tandem with a constructionist grounded theory (CGT) method, was used to maintain a strength-based approach to the research (Coghlan & Brydon-Miller, 2014), where Indigenous participants' direct expertise, experiences and perspectives concerning successful Indigenous employment outcomes are central to the research findings (Charmaz, 2000;Quinn, 2022). CGT is an adaptation of the original concept of grounded theory posited by Glaser and Strauss (1967), coined by Charmaz (2000Charmaz ( , 2006.…”
Section: Et Hodmentioning
confidence: 99%
“…This approach does not suit some research contexts, as it infers that an objective reality can be drawn from qualitative data, ignoring the historical, social and situational conditions in which the research is located in (such as may be identified within a literature review), and similarly ignoring the role of the researcher/researchers and their influence on the research (Charmaz, 2017). CGT (and grounded theory more broadly) has been utilised within several Indigenous research contexts and in conjunction with Indigenous research methodologies (Bainbridge et al, 2013;Beaufils, 2022;Quinn, 2022;Wilson et al, 2022). CGT is utilised to coconstruct a theory with participants through their data, whilst still acknowledging that the development of the research and the undertaking of the analysis is still carried out by the researcher (who is informed by their own perspectives and biases; Charmaz, 2006;Chun Tie et al, 2019;Metelski et al, 2021).…”
Section: Et Hodmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the methodological challenges of performing research and co-creating theory with members of the surf tribe who choose non-participation or are desperate to have their voices and epistemologies authentically represented are comparable with the anxieties described by advocates of IRM (Drawson et al, 2017; Nakhid-Chatoor, et al, 2018; Quinn, 2022; Wilson, 2001). Sharing and contextualizing the emotional response, such as the depth of anger and despair, emerging from performances of talk-story justifies and demonstrates the benefits of IRM as the innovative and inclusive methodological shift sought by lisahunter, Olive, Roy, and Wheaton due to the relational knowledge and accountability it demands.…”
Section: Background and Contextmentioning
confidence: 99%
“…These scholars came from a range of disciplinary backgrounds – education (Karen Martin-Booran Mirraboopa, Margaret Kovach, Linda Tuhiwai Smith, Lester-Irabinna Rigney, Miriam Rose Ungunmerr Baumann); sociology (Eva Marie Garoutte); Indigenous and feminist studies (Aileen Moreton Robinson); law (Irene Watson); and health (Lynn Lavallée, Bronwyn Fredericks, Denise Wilson, Alayne Mikahere-Hall and Juanita Sherwood). Indigenist research always begins from a principle of self-determination and is underpinned by “ceremony, respect, authentic engagement, critical reflexivity, reciprocity, relationality and responsibility” (Quinn, 2022, p. 2). Indigenist research has an entirely different epistemological and ontological foundation to all Western research traditions.…”
Section: Surveying the Research Framework For Indigenous Healthmentioning
confidence: 99%